Semicompatibility and fixed point theorems in fuzzy metric space using implicit relation - Bijendra Singh; Shishir Jain (International Journal of Mathematics and Mathematical Sciences, 2005)
The concept of semicompatibility has been introduced in fuzzy metric space and it has been applied to prove results on existence of unique common fixed point of four self-maps satisfying an implicit relation. Recently, Popa (2002) has employed a similar but not the same implicit relation to obtain a fixed point theorem for d-complete topological spaces. All the results of this paper are new.